(3WHbGJ GdabgGAs - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg hefg hMSf JhajbI s
(3hgh eNJUQ ai PcQ abgGA GdTGaYjI hefbhdI ef fSNI bQFJ Ydi GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B387 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B173 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1100s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda (B: (3Sf`I (B472s
Keywords: (3GdJGQjNs